Radioactive Source Estimation Using a System of Directional and Non-Directional Detectors - Deb, Budhaditya; Ross, J. A. F.; Ivan, A.; Hartman, M. J. (IEEE Transactions on Nuclear Science, 2011)
We derive source parameter estimation algorithms based on maximum likelihood estimation (MLE) for a system of non-directional (scintillator) and directional (CZT based Compton) radiation detectors. For multiple non-directional detectors, the joint likelihood of registered counts is maximized to estimate the source parameters. For directional detectors, the well-known List Mode Maximum Likelihood Expectation Maximization (MLEM) algorithm is extended to fuse information from multiple detectors and locate the source in Cartesian coordinates. We then develop multi-sensor fusion algorithms for a system of non-directional and directional detectors by combining MLE and MLEM algorithms. Results are presented which illustrate the behavior and performance of our proposed approaches.